AN ANALYSIS OF CLASSROOM INTERACTION IN ENGLISH TEACHING AND LEARNING PROCESS AT EIGHTH GRADE STUDENTS OF SMP IT ANNIDA LUBUKLINGGAU - bayu pratama zaidan (STKIP PGRI Lubuklinggau, 2020)
This research aimed to find and descrybe the classroom interaction in the English teaching and learning process of the Eighth class at SMP IT Annida Lubuklinggau. This research designed in a descriptive qualitative research with a naturalistic approach. The Subject of this research at SMP IT Lubuklinggau in collecting the data were observations through online systems and in-depth interviews. The result were (1) interaction in the pre-teaching which was further divided into four, namely greeting, asking students’ condition, checking students’ attendance, and telling the materials that would be learnt by the students in the meeting; (2) interaction in whilst-teaching which was further divided into three, namely motivating students to learn, rewarding the students, and helping the students learn the material; and (3) interaction in post-teaching. The interaction between the teacher and a student was divided into three (1) interaction in pre-teaching; (2) interaction in whilst- teaching which was further divided into two, namely discussing the material activity, and evaluating management activity which were divided into three, namely interaction in evaluating based on random technique, interaction based on students’ active, and interaction in evaluating based on students’ attention; and (3) interaction in post-teaching. Interaction between student and student was focused on (1) interaction in pre-teaching; (2) interaction in whilst-teaching divided into two namely, discussing the material activity, and practicing English activity; and (3) interaction in post-teaching. Interaction between the student and the material was focused on (1) interaction in pre-teaching; (2) interaction in whilst-teaching; and interaction in post-teaching.